Utility of Doppler ultrasound derived hepatic and portal venous waveforms in the management of heart failure exacerbation. Issue 8 (20th May 2020) - Singh, Shashank; Koratala, Abhilash
Abstract: Doppler ultrasound assessment of hepatic and portal vein waveforms aids in the management of patients with heart failure by noninvasively monitoring the efficacy of decongestive therapy. In the right clinical context, these waveforms can be used as an adjunct to physical examination and inferior vena cava ultrasound. Abstract : Doppler ultrasound assessment of hepatic and portal vein waveforms aids in the management of patients with heart failure by noninvasively monitoring the efficacy of decongestive therapy. In the right clinical context, these waveforms can be used as an adjunct to physical examination and inferior vena cava ultrasound.